Os impactos das condenações da Corte Interamericana de Direitos Humanos no Brasil - Ferreira, Mariana Pompilio Leonel (2020)
This dissertation aims to demonstrate that the decisions rendered by the Inter-American Court of Human Rights, judicial body of the Inter-American System, have impacts on the national scenario. The theme is extremely relevant because it demonstrates that in the face of the State’s inability to provide adequate protection of human rights, the victim can use international systems to enforce his rights. For a proper understanding of the problem, the work will be structured in four chapters. Initially it is important to understand what this regional human rights protection system is and how it works. In the following, it will be analyzed how the decisions rendered by the Inter-American Court within the States Parties to the American Convention that have agreed with their jurisdiction are effective. Subsequently, the theoretical questions that arise from the effort to understand the role of Brazil in the scenario of the Inter-American Human Rights System will be studied. Finally, a case study will analyze the convictions (which have already been supervised by the Court) of the InterAmerican Court against Brazil and their impacts on domestic law. In conclusion, although the decisions of the Court are not fully effective at the national level, they significantly impact the protection of victims’ rights. The methodology to be used in this research will essentially follow a review of the existing national and international literature on the subject, as well as a review of the Inter-American Commission merits resolutions, merits judgments, and rulings on compliance with the judgment of the Inter-American Court. which will serve as a basis for demonstrating the impact of the Court’s convictions in Brazil